Fipronil-induced cell death in salivary glands of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged females - Martins Pereira, Carolina Parga [UNESP]; de Oliveira, Patricia Rosa [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
The tick Rhipicephalus sanguineus is currently considered an urban plague. For this reason many studies are intended to find methods to control these ectoparasites. Thus, the present study analyzed the ultrastructural modifications of the salivary glands cells of semi-engorged females of R. sanguineus resulting from their exposition to Fipronil (active ingredient of Frontline (R)). The studied individuals were divided into four groups. Group 1 was exposed to distilled water (control) and groups 2, 3 and 4 were exposed to 1, 5 and 10 ppm of Fipronil, respectively. The salivary gland of ticks subjected to the acaricide showed accelerated process of cell death by atypical apoptosis, as well as augmented cell damages as the concentration of the chemical compound was increased. The acaricide toxicity at cellular level was demonstrated by remarkable changes of elements of the cytoskeleton and spherocrystals (extremely hard inorganic structures). However, tick defense mechanisms, such as the observed autofagic vacuoles proved the cells attempt to preserve their integrity and minimize the devastating action of this chemical compound on the salivary glands. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Fipronil; Cell death; Apoptotic bodies; Salivary gland